2016
DOI: 10.1038/am.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid crystalline-ITO/metal nanowire mesh transparent electrodes and their application for highly flexible perovskite solar cells

Abstract: Here, we propose crystalline indium tin oxide/metal nanowire composite electrode (c-ITO/metal NW-GFRHybrimer) films as a robust platform for flexible optoelectronic devices. A very thin c-ITO overcoating layer was introduced to the surface-embedded metal nanowire (NW) network. The c-ITO/metal NW-GFRHybrimer films exhibited outstanding mechanical flexibility, excellent optoelectrical properties and thermal/chemical robustness. Highly flexible and efficient metal halide perovskite solar cells were fabricated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 43 publications
1
78
0
Order By: Relevance
“…[97,99] As noted in Figure 9d-e, the incorporation of upper/lower conductive oxide layers of Al-doped zinc oxide (AZO) enabled efficient current collection in the area out of MeNW-networks, resulting in an improved areal charge collection. It is worth mentioning that the hybridization of MeNWs and conductive oxides gives the opportunity to achieve PSCs with device performances superior to those of their counterparts with a sole conductive oxide layer (Figure 9f,g), because MeNW-networks can act as ballistic electrical pathways, as illustrated in Figure 9d,e.…”
Section: Optoelectronic Limitation Of Menws Incorporated In Pscsmentioning
confidence: 96%
See 4 more Smart Citations
“…[97,99] As noted in Figure 9d-e, the incorporation of upper/lower conductive oxide layers of Al-doped zinc oxide (AZO) enabled efficient current collection in the area out of MeNW-networks, resulting in an improved areal charge collection. It is worth mentioning that the hybridization of MeNWs and conductive oxides gives the opportunity to achieve PSCs with device performances superior to those of their counterparts with a sole conductive oxide layer (Figure 9f,g), because MeNW-networks can act as ballistic electrical pathways, as illustrated in Figure 9d,e.…”
Section: Optoelectronic Limitation Of Menws Incorporated In Pscsmentioning
confidence: 96%
“…Owing to the presence of laterally vacant spaces between neighboring MeNWs, the intact contact is limited between highly conductive MeNWs and adjacent functional layers and hence, the collection of charge carriers is hampered when charge carriers cannot diffuse sufficiently over the cavities. [26,99] Such a phenomenon was visualized by the measurement of conductive AFM (c-AFM) for a single AgNW strand (Figure 9b-c). It clearly showed that the current only flows along the AgNW strand, while no current flow was observed in an outer region (Figure 9a,b), indicating that the cavity cannot collect charge carriers.…”
Section: Optoelectronic Limitation Of Menws Incorporated In Pscsmentioning
confidence: 99%
See 3 more Smart Citations